Competence of Ecce Teachers in Implementing the Independent Curriculum - Imrotul Ummah; Nurul Khotimah; Ruqoyyah Fitri (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2024)
The curriculum outlines how the school as a system must have clear goals and directions, especially to carry out the learning process. The development of the times causes the curriculum to continue to change from time to time. However, implementation in the field sometimes does not match what has been planned in the curriculum. One of the factors that influence it is teacher competence. Therefore, this study aims to determine the competence of early childhood education teachers implementing the Merdeka curriculum. Using a type of literature study research, this article describes how the Merdeka curriculum as the latest curriculum is implemented in ECCE units. The results showed that the competence of ECCE teachers in implementing the Merdeka curriculum can be viewed from an understanding of the curriculum, educational qualifications, and child-centered learning. In addition, the themes that emerged in this study included the efforts made by ECCE teachers and the factors supporting the success of the implementation of the Merdeka curriculum. The implications of the results of this study can be used as a guide for teachers and policy makers so that the quality of learning in ECCE can improve and be competitive.